International Crestonomy - Nasty-Marian Vladoiu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
International Crestonomy provides an innovative theoretical and practical framework regarding the enhancement of efficiency and utility in global cooperation. In this dynamic and complex world, where all international relations take place, International Crestonomy emerges as a particularly important concept, as it brings together all the principles and mechanisms for optimizing efficiency and utility in this field and, consequently, the concept becomes essential for ensuring global peace, stability, and prosperity. The objectives of International Crestonomy, which we aim to highlight in this article, are: defining and understanding the concept of International Crestonomy; identifying the fundamental principles of International Crestonomy; analyzing the challenges and perspectives of International Crestonomy and developing methods and mechanisms for optimizing efficiency and utility.